Are Patients With Schizophrenia Spectrum Disorders More Prone to Manifest Nocebo-Like-Effects? A Meta-Analysis of Adverse Events in Placebo Groups of Double-Blind Antipsychotic Trials - Palermo, Sara; Giovannelli, Fabio; Bartoli, Massimo; Amanzio, Martina (Frontiers in Pharmacology, 2019)
Background: In antipsychotic clinical trials, adverse events (AEs) are reported for the drug under evaluation to treat schizophrenia. Interestingly, patients who receive the placebo during antipsychotic trials often report several AEs, but little is known about the nature of these negative effects in patients with schizophrenia spectrum disorders (SCD). In the present meta-analysis, we evaluated the relationship between the level of psychiatric symptomatology expressed as Positive and Negative Syndrome Scale (PANSS) scores and the rates of AEs reported in the placebo arms of double-blind clinical trials, for commonly prescribed atypical antipsychotic medications. Methods: We selected 58 clinical trials describing AEs in SCD placebo groups, which compared atypical antipsychotic medications with placebo. A total of 6301 placebo-treated patients were considered. AE proﬁles of the class were clusterized using MedDRA classification and analysed using a meta-regression approach. Results: In the placebo arms the proportions of patients with any AE was 66.3% (95% CI: 62.7-69.8%). The proportion of placebo-treated patients withdrawing because of AEs was 7.2% (95% CI: 5.9-8.4%). Interestingly, the AEs in the placebo arms corresponded to those of the antipsychotic-atypical-medication-class against which the placebo was compared. Namely, using meta-regression analysis we found an association between the level of psychiatric symptomatology measured with PANSS scores and higher AEs reported as nervous system (p=.020) and gastrintestinal disorders (p=.004). Moreover, the level of a higher psychiatric symptomatology expressed with PANSS scores was also related with higher AEs associated with psychiatric symptoms (p=.017). Conclusion: These results suggest that the AEs in placebo arms of clinical trials of antipsychotic medications were substantial. Importantly, a higher level of psychiatric symptomatology makes SCD patients more prone to express AEs, thus contributing to possible drop-outs and to a lower adherence to treatments. These ﬁndings are in accordance with the expectation theory of placebo and nocebo effects.